Enhanced Schedulability Analysis of Hard Real-Time Systems on Power Manageable Multi-Core Platforms - He, Da; Müller, Wolfgang (Third International Symposium on Advances in Embedded Systems and Applications (ESA-2012))

Compilation of Methodologies to Speed up the Verification Process at System Level - Radke, Stephan; Rülke, Steffen; Oliveira, Marcio F.; Kuznik, Christoph; Müller, Wolfgang; Ecker, Wolfgang; Esen, Volkan; Hufnagel, Simon; Bannow, Nico; Oetjens, Jan-Hendrik; Brazdrum, Helmut; Janssen, Peter; et al. (edaWorkshop 12)

Process integrated wire-bond quality control by means of cytokine-Formal Immune Networks - Montealegre, Norma; Hagenkötter, Sebastian (Journal of Intelligent Manufacturing 23(3))

Towards Adaptive Resource Management for Virtualized Real-Time Systems - Grösbrink, Stefan; Oberthür, Simon; Baldin, Daniel (4th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2012))

Online Model Checking for Dependable Real-time Systems - Zhao, Yuhong; Rammig, Franz-Josef (16th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing-Shenzhen, China)

Agent-Based Modeling and Simulation of Artificial Immune Systems - Montealegre, Norma; Rammig, Franz-Josef (Third IEEE Workshop on Self-Organizing Real-Time Systems (SORT 2012))

Self-Coordination as Fundamental Concept for Cyber Physical Systems - Rammig, Franz-Josef (2nd SBC Workshop on Autonomic Distributed Systems - WoSiDA 2012)

Planarization of Geographic Cluster-based Overlay Graphs in Realistic Wireless Networks - Mathews, Emi (Ninth International Conference On Information Technology : New Generations (ITNG))

Online Energy-Efficient Hard Real-Time Scheduling for Component Oriented Systems - He, Da; Müller, Wolfgang (2012 IEEE 15th International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing (ISORC))

Efficient Alignment of Aerial Images Based on Virtual Forces - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (Proceedings of The Eighth International Conference on Autonomic and Autonomous Systems (ICAS))
Getting a contemporary aerial overview of a disaster area is a foremost task in search and rescue operations. We previously have introduced a novel method for registering a large amount of aerial images when camera parameters are almost unknown and no reference images are available. This paper provides two new methods, which improve our method for image registration based on virtual forces. The goal is to improve the performance of creating a contemporary overview map of a disaster area assembling several images taken by unmanned aerial vehicles (UAVs) equipped with cameras. In this paper, two new methods are introduced: a method for rotation estimation and a method for scale estimation. Both methods use fast heuristic approximation approaches and statistical methods to provide high robustness. We discuss the methods in detail and compare them to our previous approach regarding robustness and calculation speed. We can show that the new methods significantly increase the performance of the image registration process.

Efficient Color-Based Image Segmentation and Feature Classification for Image Processing in Embedded Systems - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa; Bieshaar, Maarten (Proceedings of the 4th International Conference on Resource Intensive Applications and Services (INTENSIVE))
In this paper, a color based feature extraction and classification approach for image processing in embedded systems in presented. The algorithms and data structures developed for this approach pay particular attention to reduce memory consumption and computation power of the entire image processing, since embedded systems usually impose strong restrictions regarding those resources. The feature extraction is realized in terms of an image segmentation algorithm. The criteria of homogeneity for merging pixels and regions is provided by the color classification mechanism, which incorporates appropriate methods for defining, representing and accessing subspaces in the working color space. By doing so, pixels and regions with color values that belong to the same color class can be merged. Furthermore, pixels with redundant color values that do not belong to any pre-defined color class can be completely discarded in order to minimize computational effort. Subsequently, the extracted regions are converted to a more convenient feature representation in terms of statistical moments up to and including second order. For evaluation, the whole image processing approach is applied to a mobile representative of embedded systems within the scope of a simple real-world scenario.

Dynamic Resource Management for Virtualized Mixed-Criticality Systems - Grösbrink, Stefan; Oberthür, Simon; Baldin, Daniel (Quo Vadis, Virtual Platforms? (in conjunction with Design, Automation and Test in Europe DATE 2012))

A SystemC Library for Advanced TLM Verification - Oliveira, Marcio F.; Kuznik, Christoph; Müller, Wolfgang; Ecker, Wolfgang; Esen, Volkan (Proceeding of Design and Verification Conference (DVCON))

A model-driven engineering framework for embedded systems design - Nascimento, Francisco A. M.; Oliveira, Marcio F.; Wagner, Flavio (Innovations in Systems and Software Engineering 8)

MOUSSE: scaling MOdelling and verification to complex heterogeneoUS embedded Systems Evolution - Becker, Markus; Gnokam Defo, Gilles Bertrand; Müller, Wolfgang; Fummi, F.; Pravadelli, G.; Vinco, Sara (Design, Automation and Test in Europe (DATE 2012))

XEMU: A QEMU Based Binary Mutation Testing Framework - Becker, Markus; Kuznik, Christoph; Joy, M. tech. Mabel; Xie, Tao; Müller, Wolfgang (Design, Automation and Test in Europe DATE)

Real-Time Android: Deterministic Ease of use - Mauerer, Wolfgang; Hillier, Gernot; Sawallisch, Jan; Hönick, Stefan; Oberthür, Simon (Proceedings of Embedded World Conference)

Image Segmentation For Object Detection on a Deeply Embedded Miniature Robot - Jungmann, Alexander; Schierbaum, Thomas; Kleinjohann, Bernd (Proceedings of the Seventh International Conference on Computer Vision Theory and Applications (VISAPP))
In this paper, an image segmentation approach for object detection on the miniature robot BeBot - a deeply embedded system - is presented. In order to enable the robot to detect and identify objects in its environment by means of its camera, an efficient image segmentation approach was developed. The fundamental algorithm bases on the region growing and region merging concept and identifies homogeneous regions consisting of adjacent pixels with similar color. By internally representing a contiguous block of pixels in terms of run-lengths, the computational effort of both the region growing and the region merging operation is minimized. Finally, for subsequent object detection processes, a region is efficiently translated into a statistically feature representation based on discretized moments.

Deterministic Runtime Adaptation for Hard Real-time Embedded Systems with Processing Constraints - Bin Tariq, Fahad (Proceedings of the 2nd International Conference on Pervasive Embedded Computing and Communication Systems)

A Localized Link Removal and Addition based Planarization Algorithm - Mathews, Emi; Frey, Hannes (13th International Conference On Distributed Computing And Networking (ICDCN))

Deployment of mobile routers ensuring coverage and connectivity - Mathews, Emi; Mathew, Ciby (International Journal of Computer Networks and Communications 4(1))

Virtual Prototyping of Cyber-Physical Systems - Müller, Wolfgang; Becker, Markus; Zabel, Henning; Elfeky, Ahmed; DiPasquale, Anthony (In Proceedings of 17th Asia and South Pacific Design Automation Conference (ASP-DAC 2012)

Swarm Robotic Time Synchronization for Object Tracking - Khaluf, Yara; Mathews, Emi; Rammig, Franz-Josef (Self-Organization in Embedded Real-Time Systems)

Biologically Inspired Information Technology: Towards a Cyber Biosphere - Rammig, Franz-Josef (Schemata und Praktiken)

Adaptive Web Services for Modular and Reusable Software Development - Bin Tariq, Fahad; Korrapati, Sandeep (Kapitel: F-DRARE: A Framework for Deterministic Runtime Adaptation of Cyber Physical Systems)

Towards an Integrated Service Rating and Ranking Methodology for Quality Based Service Selection in Automatic Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the Fourth International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
The paradigm shift from purchasing monolithic software solutions to a dynamic composition of individual solutions entails many new possibilities yet great challenges, too. In order to satisfy user requirements, complex services have to be automatically composed of elementary services. Multiple possibilities of composing a complex service inevitably emerge. The problem of selecting the most appropriate services has to be solved by comparing the different service candidates with respect to their quality in terms of inherent non-functional properties while simultaneously taking the user requirements into account.We are aiming for an integrated service rating and ranking methodology in order to support the automation of the underlying decision-making process. The main contribution of this paper is a first decomposition of the quality-based service selection process, while emphasizing major issues and challenges, which we are addressing in the On-The-Fly Computing project.

Towards the Application of Reinforcement Learning Techniques for Quality-Based Service Selection in Automated Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Services Computing (SCC))
A major goal of the On-The-Fly Computing project is the automated composition of individual services based on services that are available in dynamic markets. Dependent on the granularity of a market, different alternatives that satisfy the requested functional requirements may emerge. In order to select the best solution, services are usually selected with respect to their quality in terms of inherent non-functional properties. In this paper, we describe our idea of how to model this service selection process as a Markov Decision Process, which we in turn intend to solve by means of Reinforcement Learning techniques in order to control the underlying service composition process. In addition, some initial issues with respect to our approach are addressed.

Master Election for Time Synchronization in Swarm Robotic Systems - Khaluf, Yara; Weiss, Fabian; Micus, Sebastian (The 10th IEEE International Symposium on Parallel and Distributed Processing with Applications)

Connectivity of Autonomous Agents Using Ad-hoc Mobile Router Networks - Mathews, Emi; Mathew, Ciby (Third International Conference on Networks & Communications, LNICST)

Optimal Scheduling of Information Extraction Algorithms - Wachsmuth, Henning; Stein, Benno (Proceedings of COLING 2012: Posters)

Certifying RSA - Kakvi, Saqib; Kiltz, Eike; May, Alexander (Advances in Cryptology – ASIACRYPT 2012)

Optimal Security Proofs for Full Domain Hash, Revisited - Kakvi, Saqib; Kiltz, Eike (Advances in Cryptology – EUROCRYPT 2012)

StreamKM++: A clustering algorithm for data streams - Ackermann, Marcel Rudolf; Märtens, Marcus; Raupach, Christoph; Swierkot, Kamil; Lammersen, Christiane; Sohler, Christian

Turing und Kryptografie - Blömer, Johannes (Informatik-Spektrum)
Ich beschreibe die deutsche Enigma-Verschlüsselungsmaschine und skizziere, wie sie von den Codebrechern von Bletchely Park um Alan Turing gebrochen wurde. Besonderes Augenmerk lege ich auf die Beiträge Alan Turings und die Bedeutung seiner Leistung für die Entwicklung moderner Kryptografie.

On black-box models of computation in cryptology - Jager, Tibor

On the Security of TLS-DHE in the Standard Model - Jager, Tibor; Kohlar, Florian; Schäge, Sven; Schwenk, Jörg (Advances in Cryptology - CRYPTO 2012 - 32nd Annual Cryptology Conference, Santa Barbara, CA, USA, August 19-23, 2012. Proceedings)

Tightly Secure Signatures and Public-Key Encryption - Hofheinz, Dennis; Jager, Tibor (Advances in Cryptology - CRYPTO 2012 - 32nd Annual Cryptology Conference, Santa Barbara, CA, USA, August 19-23, 2012. Proceedings)

Bleichenbacher's Attack Strikes again: Breaking PKCS#1 v1.5 in XML Encryption - Jager, Tibor; Schinzel, Sebastian; Somorovsky, Juraj (Computer Security - ESORICS 2012 - 17th European Symposium on Research in Computer Security, Pisa, Italy, September 10-12, 2012. Proceedings)

Waters Signatures with Optimal Security Reduction - Hofheinz, Dennis; Jager, Tibor; Knapp, Edward (Public Key Cryptography - PKC 2012 - 15th International Conference on Practice and Theory in Public Key Cryptography, Darmstadt, Germany, May 21-23, 2012. Proceedings)

Proving Linearizability of Multiset with Local Proof Obligations - Travkin, Oleg; Wehrheim, Heike; Schellhorn, Gerhard (ECEASST)

Model evolution and refinement - Ruhroth, Thomas; Wehrheim, Heike (Sci. Comput. Program.)

How to Prove Algorithms Linearisable - Schellhorn, Gerhard; Wehrheim, Heike; Derrick, John (Computer Aided Verification - 24th International Conference, CAV 2012, Berkeley, CA, USA, July 7-13, 2012 Proceedings)

Computer science and society as a field of computer science - Engbring, Dieter; Selke, Harald
In this article we report on the experiences of a redesigned teaching in the field of computer science and society (IuG). The reasons for the redesign and the concept are outlined. We have condensed our experiences into theses: 1. Computer science and society should be a compulsory course in the bachelor's degree, in which students get an overview of which social framework conditions are relevant for them and how they can be incorporated into practice. 2. Historical contents of computer science are to be processed here by considering current developments in the context of their genesis.

User Centered Design of an Interactive Mobile Assistance and Supervision System for Rehabilitation Purposes - Klompmaker, Florian; Workowski, Anke; Thronicke, Wolfgang; Ostermair, Florian; Willemsen, Detlev; Hoffmann, D

Towards Multimodal 3D Tabletop Interaction using Sensor Equipped Mobile Devices - Klompmaker, Florian; Nebe, Karsten; Eschenlohr, Julien

The technical potential of digital boards - Selke, Harald; Winkelnkemper, Felix
This article explains the technical potential of digital boards with which more and more schools are being equipped. A consideration of current usage scenarios of these interactive whiteboards shows that a large part of this potential is still unused and the deficits of the software often have to be circumvented with tricks, especially for use in demanding, student-oriented lessons. Finally, the further development of existing teaching scenarios using this technical potential shows that considering the technical possibilities of digital boards can motivate new didactic scenarios.

Der Qualitätsstandard für Usability Engineering der German UPA - Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut

Base Requirements for Virtual Tabletop Groupware Artifacts - Tobias, Müller; Nebe, Karsten; Klompmaker, Florian

Collaborative work on interactive displays - design, operation and fields of application - Fischer, Holger Gerhard; Klompmaker, Florian (M & C, humans and computers)

Das Heinz Nixdorf Institut: Über 25 Jahre interdisziplinär erfolgreich - Keil, Reinhard

EVALUATION OF WHOLE-BODY NAVIGATION AND SELECTION TECHNIQUES IN IMMERSIVE 3D ENVIRONMENTS - Klompmaker, Florian; Dridger, Alexander; Nebe, Karsten (Proceedings of the ASME 2012 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)
Since 2010 when the Microsoft Kinect with its integrated depth-sensing camera appeared on the market, completely new kinds of interaction techniques have been integrated into console games. They don’t require any instrumentalization and no complicated calibration or time-consuming setup anymore. But even having these benefits, some drawbacks exist. Most games only enable the user to fulfill very simple gestures like waving, jumping or stooping, which is not the natural behavior of a user. In addition the depth-sensing technology lacks of haptic feedback. Of course we cannot solve the lack of haptic feedback, but we want to improve the whole-body interaction. Our goal is to develop 3D interaction techniques that give a maximum of freedom to the user and enable her to perform precise and immersive interactions. This work focuses on whole-body interaction in immersive virtual environments. We present 3D interaction techniques that provide the user with a maximum of freedom and enables her to operate precisely and immersive in virtual environments. Furthermore we present a user study, in which we analyzed how Navigation and Manipulation techniques can be performed by users’ body-interaction using a depth-sensing camera and a huge projection screen. Therefore three alternative approaches have been developed and tested: classical gamepad interaction, an indirect pointer-based interaction and a more direct whole- body interaction technique. We compared their effectiveness and preciseness. It turned out that users act faster, while using the gamepad, but generate significantly more errors at the same time. Using depth-sensing based whole-body interaction techniques it became apparent, that the interaction is much more immersive, natural and intuitive, even if slower. We will show the advantages of our approach and how it can be used in various domains, more effectively and efficiently for their users.

Integrating Usability Engineering in the Software Development Lifecycle Based on International Standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS), Copenhagen, Denmark)

Summary and Outlook - Keil, Reinhard; Metternich, Hans-J {\ "u} rgen; Ritzenhoff, Steffan

Durchl {\ "a} ssigkeitsorientierte Bildung - Keil, Reinhard; Niehus, Dominik; Ossenschmidt, Daniel

Automatic emotion recognition - technologies, interpretation and applications - Brand, Marcel; Klompmaker, Florian; Schleining, Peter; Weiss, Fabian (Computer science spectrum)

Passability in education - a challenge for ü r the future - Keil, Reinhard; Metternich, Hans-J {\ "u} rgen; Ritzenhoff, Steffan

Enriching Disaster Control Management based on Human-Centered Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM), Vancouver, Kanada)

German UPA Qualitätsstandard für Usability Engineering - Behrenbruch, Kay; Bogner, Christian; Fischer, Holger Gerhard; Geis, Thomas; Geitner, Claudia; Heimgärtner, Rüdiger; Hofmann, Britta; Hunkirchen, Peter; Kluge, Oliver; Litzenberg, Britta; Molich, Rolf; Polkehn, Knut; et al.

Learning scenarios for school 2.0 - Jakoblew, Marcel; Niehus, Dominik; Selke, Harald
In order to support everyday school life, the educational platform "Education in Dialogue" was developed and continuously improved over a period of more than ten years in an evolutionary process with user participation. The aim of this article is to show how sustainable support can be achieved by not focusing on the basic possibilities of network-based work, but using everyday practice as a starting point. In order to decide how the school assignment can be optimally supported in a specific embodiment, we develop »learning scenarios«. Based on a didactic approach, a technical concept and a usage guide are designed.

E-learning strategies: best practice or careful structural renewal? - Keil, Reinhard; Schild, Christian; Winkelnkemper, Felix

dSensingNI – A Framework for Advanced Tangible Interaction using a Depth Camera - Klompmaker, Florian; Nebe, Karsten; Fast, Alex
This work presents an approach to overcome the disadvantages of existing interaction frameworks and technologies for touch detection and object interaction. The robust and easy to use framework dSensingNI (Depth Sensing Natural Interaction) is described, which supports multitouch and tangible interaction with arbitrary objects. It uses images from a depth-sensing camera and provides tracking of users fingers of palm of hands and combines this with object interaction, such as grasping, grouping and stacking, which can be used for advanced interaction techniques.

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI), Valencia, Spanien)

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI), Valencia, Spanien)

Computer science and society - a lecture in the master's degree in computer science - Selke, Harald (FIfF communication)
There have been and still are lectures on the subject of computer science and society at some universities. Some of these are still held by those who can be considered the founders of this subject in Germany. In recent years, however, some of the protagonists from the very beginning have already retired and the positions have been filled or partially rededicated with successors of various origins. Aspects that were previously dealt with within this subject are now addressed in other subjects. For the "new" lecturers the question arises how the problem that Stefan Köpsell formulated very honestly can be addressed: "Since I have not yet known any satisfactory systematics for computer science and society, the lecture consists of a collection of widely spread, each separately understandable themed mosaic tiles. Everyone has to put their overall understanding of the topic together personally. ”(Köpsell, 2012) In this contribution, attempts to design a lecture Computer Science and Society within the given framework (previous lectures, content-related delimitation of other events, supplementary events, previous knowledge and Expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress. delimitation of the content of other events, supplementary events, previous knowledge and expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress. delimitation of the content of other events, supplementary events, previous knowledge and expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress.

Interdisciplinary {\ "a} t as a challenge for ü r e-learning research - Keil, Reinhard; Wessner, Martin (i -com magazine f {\ "u} r interactive and cooperative media)

Between innovation and suitability for everyday use - "Lernstatt Paderborn" - Keil, Reinhard (Paderborn University {\ "a} ts-Zeitschrift)

A coactive support approach for {\ "u} r processes of social reality construction in product creation processes - Holzwei {\ ss} ig, Kai

FPGA-based design and implementation of an approximate polynomial matrix EVD algorithm - Kasap, Server; Redif, Soydan (Proc. Int. Conf. on Field Programmable Technology (ICFPT))

Semi-automatic establishment and maintenance of valid traceability in automotive development processes - Fockel, Markus; Holtmann, Jörg; Meyer, Jan (2012 Second International Workshop on Software Engineering for Embedded Systems (SEES))
The functionality realized by software in modern cars is increasing and as a result the development artifacts of automotive systems are getting more complex. The existence of traceability along these artifacts is essential, since it allows to monitor the product development from the initial requirements to the final code. However, traceability is established and maintained mostly manually, which is time-consuming and error-prone. A further crucial problem is the assurance of the validity of the trace links, that is, the linked elements are indeed related to each other. In this paper we present a semiautomatic approach to create, check, and update trace links between artifacts along an automotive development process.

FPGA implementation of a second-order convolutive blind signal separation algorithm - Kasap, Server; Redif, Soydan (Int. Architecture and Engineering Symp. (ARCHENG))

Comparison of Bayesian Move Prediction Systems for Computer Go - Wistuba, Martin; Schaefers, Lars; Platzner, Marco (Proc. IEEE Conf. on Computational Intelligence and Games (CIG))

A Data Driven Science Gateway for Computational Workflows - Grunzke, Richard; Birkenheuer, Georg; Blunk, Dirk; Breuers, Sebastian; Brinkmann, André; Gesing, Sandra; Herres-Pawlis, Sonja; Kohlbacher, Oliver; Krüger, Jens; Kruse, Martin; Müller-Pfefferkorn, Ralph; Schäfer, Patrick; et al. (Proc. UNICORE Summit)

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, Reuven; Nudelman, Ilia; Polevoy, Gleb (Infocom'2012, Orlando, Florida)

Editorial for Algorithmic Aspects of Wireless Sensor Networks - Dolev, Shlomi; Scheideler, Christian (Theor. Comput. Sci.)

Selfish Distributed Optimization - Monien, Burkhard; Scheideler, Christian (Euro-Par 2012 Parallel Processing - 18th International Conference, Euro-Par 2012, Rhodes Island, Greece, August 27-31, 2012. Proceedings)

Application and Evaluation in the Automotive Domain - Fockel, Markus; Heidl, Peter; Höfflinger, Jens; Hönninger, Harald; Holtmann, Jörg; Horn, Wilfried; Meyer, Jan; Meyer, Matthias; Schäuffele, Jörg (Model-Based Engineering of Embedded Systems)
This chapter summarizes the application and evaluation of the SPES engineering methodology in the automotive domain. After introducing the particular domain characteristics, we state some research questions that we have investigated. Some of the activities that address these research questions are presented in detail. We conclude that the SPES engineering methodology is a good basis for the development of automotive systems, but could be further refined to fit the particular needs of the domain.

Jamming-resistente MAC-Protokolle - Meith, Frank Ingo

Mobile WDM Backhaul Access Networks with Physical Inter-Base-Station Links for Coordinated Multipoint Transmission/Reception Systems - Biermann, T.; Scalia, L. (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011)

Coordinated multipoint multiuser-MIMO transmissions over backhaul-constrained mobile access networks - Choi, Changsoon; Scalia, Luca; Biermann, Thorsten; Mizuta, Shinj (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications)

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Proceedings of the 1st German-Malaysian Workshop, Hannover, 27. - 29. Jun. 2012)

STIR: Software for Tomographic Image Reconstruction Release 2 - Thielemans, Kris; Tsoumpas, Charalampos; Mustafovic, Sanida; Beisel, Tobias; Aguiar, Pablo; Dikaios, Nikolaos; W Jacobson, Matthew (Physics in Medicine and Biology)

Parallel algorithm for computation of second-order sequential best rotations - Redif, Soydan; Kasap, Server (Int. Journal of Electronics)

Parallel Processor Design and Implementation for Molecular Dynamics Simulations on a FPGA Parallel Computer - Kasap, Server; Benkrid, Khaled (Journal of Computers)

Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid Rose (FIfF-Kommunikation)
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Introducing Google Chart Tools and Google Maps API in Data Visualization Courses - Zhu, Y. (IEEE Computer Graphics and Applications)

Teaching 3D Computer Animation to Illustrators: The Instructor as Translator and Technical Director - Koning, W. F. (IEEE Computer Graphics and Applications)

Large-Scale Visualization Projects for Teaching Software Engineering - Müller, C.; Reina, G.; Burch, M.; Weiskopf, D. (IEEE Computer Graphics and Applications)

Visualization Curriculum Panel - or The Changes We Have Made to Our Visualization Courses Over the Last 10 Years - Domik, Gitta; Ebert, David; Kohlhammer, Jörn; Rushmeier, Holly; Santos, Beatriz Sousa; Weiskopf, Daniel (Eurographics 2012 - Education Papers)

Leveraging Multidisciplinarity in a Visual Analytics Graduate Course - Elmqvist, N.; Ebert, D. S. (IEEE Computer Graphics and Applications)

Digital Media and the Beginning Designer - Goldman, G. (IEEE Computer Graphics and Applications)

Fostering Collaboration and Self-Motivated Learning: Best Practices in a One-Semester Visualization Course - Domik, Gitta (IEEE Computer Graphics and Applications)

Graph Transformation - 6th International Conference, ICGT 2012, Bremen, Germany, September 24-29, 2012, Proceedings

CoMP clustering and backhaul limitations in cooperative cellular mobile access networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (Pervasive and Mobile Computing)

Segment-based packet combining: how to schedule a dense relayer cluster? - Willig, Andreas; Karl, Holger; Kipnis, Danil (Wireless Networks)

Average and competitive analysis of latency and power consumption of a queuing system with a sleep mode - Herlich, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Energy-Efficient Computing and Networking, e-Energy'12, Madrid, Spain, May 9-11, 2012)

Energy Efficient Clustering using a Wake-up Receiver - Blanckenstein, Johannes; Klaue, Jirka; Karl, Holger (European Wireless 2012 - 18th European Conference 2012, April 18-20, 2012, Poznan, Poland.)

On Local Separation of Processing and Storage in Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 9th International Conference, GECON 2012, Berlin, Germany, November 27-28, 2012. Proceedings)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks, Workshop Proceedings, Clearwater Beach, FL, USA, October 22-25, 2012)

Cooperating base station set selection and network reconfiguration in limited backhaul networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger; Kellerer, Wolfgang (23rd IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2012, Sydney, Australia, September 9-12, 2012)